Analysis of ICT Framework of Junior High School Teachers in Depok City in Supporting In-depth Learning: (Study on Schools Receiving Operational Assistance for School Performance 2025) - Yulaikhah, Siti; Suharyati, Henny (Edumedia Solution, 2025)
This study aims to analyze the readiness of junior high school teachers receiving the 2025 Performance-Based School Operational Assistance (BOS Kinerja) in utilizing Information and Communication Technology (ICT) to support deep learning. A total of 100 teachers from various public and private schools participated in the study. Data were collected using a questionnaire based on the UNESCO ICT Competency Framework for Teachers and analyzed using quantitative descriptive methods. The results indicate that teachers' readiness in the domains of knowledge acquisition (KA) and knowledge deepening (KD) to support deep learning falls into the